2021
DOI: 10.3390/pharmaceutics13081235
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Coating Reduces the Leakage of Melittin Encapsulated in Liposomes and Increases Targeted Delivery to Melanoma Cells

Abstract: Melittin is a promising antitumor substance; however, it is a nonspecific cytolytic peptide, which limits its clinical application. In this study, melittin liposomes (Mel-Lip) and hyaluronic acid (HA)-modified Mel-Lip (Mel-HA-Lip) were designed to reduce the toxicity and increase the anti-tumor effects of melittin. The optimal preparation procedure was evaluated using a uniform design based on the single factor method, and the concentration of HA was determined based on the cellular uptake of coumarin 6 labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…HA is widely used in the management of DED. Is a naturally occurring, endogenous, glycosaminoglycan polymer present in various tissue fluids in human body, mainly in the extracellular matrix [ 72 ]. In particular, high molecular weight HA (>1000 kDa) was reported to have some immunosuppressive, antioxidant, anti-inflammatory, anti-angiogenic effect, and wound repair capacity [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…HA is widely used in the management of DED. Is a naturally occurring, endogenous, glycosaminoglycan polymer present in various tissue fluids in human body, mainly in the extracellular matrix [ 72 ]. In particular, high molecular weight HA (>1000 kDa) was reported to have some immunosuppressive, antioxidant, anti-inflammatory, anti-angiogenic effect, and wound repair capacity [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Unfortunately, the use of a liposome formulation is not suitable for Mel delivery because the phospholipid composition of the vesicle can be disrupted by Mel, leading to drug leakage. 30,31 Hence, the niosomal vesicle approach, which is based mainly on the use of surfactant solutions, is the most promising solution. Niosomes, which are analogs of liposomes, are a self-assembly of non-ionic surfactants and lipids such as cholesterol, making them capable of entrapping both hydrophilic and lipophilic substances.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle-based drug delivery systems can be used to encapsulate drugs or therapeutic substances and serve as a carrier that protects the drug or substance from interacting with unfavorable environments and reduces their toxicity. [23][24][25][26] Previously, several delivery systems have been introduced to encapsulate Mel by different nanocarriers 27,28 including lipid-based systems such as liposomes [29][30][31] and niosomes. 32 Because of the drawback of liposome-related unstable structures resulting in drug leakage, 30,31 niosome-based drug delivery systems have become a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments revealed that this material has a significant inhibitory effect on the survival of hepatocellular carcinoma (HCC) cells and suppresses the growth of subcutaneous and orthotopic liver cancer transplantation tumors in vivo. A recent attempt used a liposome modified with dioleoyl-phosphoethanolamine (DOPE)-coupled HA (HA-DOPE) to deliver MEL; the HA layer on the surface of liposome entraps MEL and prevents it from leakage [ 99 ]. However, the outer-surface modification of liposomes may exert a limited effect in preventing MEL from affecting the lipid bilayer structure of liposomes.…”
Section: Delivery Vehicles For Melittinmentioning
confidence: 99%